Synthesis of high alumina ZSM-5 molecular sieve with ethylene diamine as template - Venkatathri, N. (Journal of the Indian Chemical Society, 2006)
Attempts were made to investigate compositional constraints in the synthesis of pentasill molecular sieves, including aluminosilicate zeolites using ethylene diamine (C2DN) template, from the gel composition 1.85Na(2)O : aAl(2)O(3) : 15.2SiO(2) : 592H(2)O : 19.7C(2)DN in the temperature 177 degrees C for ten days. When a = 0.25 the product was ZSM-5 and then a = 1 the product was ZSM-35 and in between compositions the mixture of two were obtained. Reduce the time of crystallization time to 5 days give nanocrystalline material. XRD and FT-IR spectra in framework region of ZSM-5 synthesized using ethylene diamine template and without template are having similar pattern, however the intensity varies. Scanning electron microscopic picture of the both are varies. The structural stability of the zeolite ZSM-5 synthesized using no template was also found to be lower as compared with that for the ZSM-5 synthesized using ethylene diamine template. These differences. may result from the occluded excess sodium.
Keywords: ethylenediamine; Molecular sieve; zeolite